2011
DOI: 10.1590/s0103-84782011005000127
|View full text |Cite
|
Sign up to set email alerts
|

Espectro de gotas e idade de trifólios na taxa de absorção e efeito residual de fungicidas em soja

Abstract: RESUMO O objetivo do presente trabalho foi avaliar o efeito de espectros de gotas (grossas, médias e finas) na velocidade de absorção de fungicidas, para trifólios de diferentes idades através de medida indireta expressa pelo residual de controle de ferrugem asiática da soja (Phakopsora pachyrhizi INTRODUÇÃOA ferrugem asiática, causada pelo fungo Phakopsora pachyrhizi Sidow, constitui-se na principal doença da cultura da soja, já que as condições climáticas são favoráveis ao patógeno. Na maioria das regiões, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
7
0
6
Order By: Relevance
“…Since the motion of most fungicides is acropetal (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011 andLENZ et al 2011), spraying the base of plants suggests significantly a more effective control of the diseases when compared to sprayings by tips distant from the apex of soybean plants. However, experimental results indicate that the aggregation of such technology in aerial spraying of fungicide from soybean -isolated or in combination with conventional sprayings -did not differ significantly from the spraying by nozzles on the culture; thus refuting the assumptions that justify the use of such technology application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the motion of most fungicides is acropetal (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011 andLENZ et al 2011), spraying the base of plants suggests significantly a more effective control of the diseases when compared to sprayings by tips distant from the apex of soybean plants. However, experimental results indicate that the aggregation of such technology in aerial spraying of fungicide from soybean -isolated or in combination with conventional sprayings -did not differ significantly from the spraying by nozzles on the culture; thus refuting the assumptions that justify the use of such technology application.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, it is here that the coverage and penetration of the fungicide are more adversely affected by the leaf weight of tops to form a barrier spraying, favoring the pathogen (ALMEIDA et al 2,005;CALLA et al 2,009;REIS et al, 2010;CUNHA et al, 2011). Like most systemic fungicides suitable for chemical control of soybean foliar diseases move in the direction of the base to the apex of the plant, the leaves of the lower third of the plant become the target of spraying (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011;LENZ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the uniform coverage assumes a satisfactory distribution of pulverized or sprayed liquid characterized by low coefficients of variation of surface volumetric distribution regarding tip sets (Cunha & Silva, 2010). Tips or nozzles with higher density provide greater leaf area coverage and subsequently, efficient absorption (Lenz et al, 2011). However, our results showed that for example, tips such as XR 11001 that generate higher droplet density did not efficiently control the Asian soybean rust disease.…”
Section: Resultsmentioning
confidence: 59%
“…In this regard, fine droplet spectrum provides an efficient deposition, control of the Asian soybean rust, and productivity, regardless of the soybean cultivar assessed (Debortoli et al, 2012). Such droplets have a higher fungicide absorption rate (Lenz, Balardin, Minuzzi, Tormen & Marques, 2011), and higher penetration on soybean plant canopy (Román, Cortez, Ferreira & Oliveira, 2009). According to Debortoli et al, (2012), a fine droplet spectrum (<200 μm) gives efficient results in terms of droplet deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Inoculation was based on the methodology used by Lenz et al (2011). Urediniospores of P. pachyrhizi were at the concentration of 2 x10 5 spores ml -1 of distilled water plus Tween adhesive spreader (80 ppm).…”
Section: Application Of Treatment and Pathogen Inoculationmentioning
confidence: 99%